ANALISIS PENGARUH SEKTOR EKONOMI UNGGULAN TERHADAP PERTUMBUHAN EKONOMI KABUPATEN KUANTAN SINGINGI - Zul Ammar (JURNAL EKONOMI AL-KHITMAH, 2023)
This research was conducted in Kuantan Singingi Regency with the aim of knowing and analyzing the influence of leading economic sectors on economic growth in Kuantan Singingi Regency. In this study using a type of quantitative descriptive research with a development planning model. The data used is time series data, namely PDRB data for Kuantan Singingi Regency from 2016 to 2020 which will be analyzed using an analytical tool, namely Multiple Linear Regression. The results of the analysis show that the first entire sector is agriculture, forestry and fisheries, the second is the water supply sector, waste management, waste and recycling, the third is the government administration sector, defense and compulsory social security, the fourth is the education services sector and the fifth is the manufacturing industry sector which has a significant effect in increasing the economic growth of Kuantan Singingi Regency. Keywords: Economic growth, PDRB, Multiple Linear Regression